The Role Of School Conselors In Advocacy Services - Hermawan, Rio; Pransiska, Roni (International Journal of Applied Guidance and Counseling, 2020)
The main role of School Counselors in the Era of the Indonesian Revolution 4.0, is expected to formulate various types of counseling guidance services that are appropriate to the needs of students in this era. One type of school counselor services in providing services to students needed in this era is an advocacy service that refers to Permendikbud No. 111 (2014) although in this regulation we only get very limited information about advocacy, but it is expected that in its implementation, school counselors will be able to interpret and carry out advocacy at the micro and macro levels. Counselors should be able to: (1) empower students by helping them develop advocacy skills, (2) conduct relevant negotiation efforts to help students access resources, (3) build collaborative relationships with relevant community institutions to overcome various challenges, ( 4) implementing advocacy ideas at the system level, (5) communicating relevant information to the public, and (6) engaging in social / political advocacy activities. Advocacy services are counselor services in schools that are intended to assist students who experience non-educational, discriminatory, malpractice, violence, harassment, and criminal behavior. The function of counselor services in advocacy services, helps students gain learning about their rights and / or interests that are not getting much attention. Therefore, the role of counselors in advocacy services is very important in the process of counseling guidance services in schools. So the counselor must have the ability to guide students well. In order for counselors to be able to provide optimal guidance services to students, the counselor must be able to understand the characteristics of the counselee.